Solution-processed pristine metal oxides as electron-transporting materials for perovskite solar cells - Sharma, Harshit; Srivastava, Ritu (Frontiers in Electronic Materials, 2023)
In recent years, perovskite material-based photovoltaic devices have attracted great attention of researchers because of an expeditious improvement in their efficiency from 3.8% to over 25%. The electron transport layer (ETL), which functions for the extraction and transportation of photogenerated electrons from active perovskite material to the electrodes, is a vital part of these perovskite solar cells (PSCs). The optoelectronic properties of these electron transport layer materials also have an impact on the performance of these perovskite solar cells, and for commercialized flexible perovskite solar cells, low-temperature and solution-processable electron transport layers having high stability and suitable optoelectronic properties are needed. In this regard, the solution-processable films of different metal oxides have been largely investigated by many research groups. So, this review summarizes the optoelectronic properties of the different metal oxide-based electron transport layers and the development in the performance of the perovskite solar cells, which have solution-processable metal oxides as electron transport layers.